PEMANFAATAN KOTORAN SAPI SEBAGAI BAHAN BIOGAS SKALA RUMAH TANGGA ANGGOTA SUBAK BANYUMATI DESA UMA ANYAR SERIRIT BULELENG - Suardana, P.; Sumadiyasa, M.; Suharta, W. G.; Ngr. Gunawan, A. A.; Suarbawa, K. N. (Buletin Udayana Mengabdi; Vol 16 No 1 (2017), 2018)
Has conducted socialization to community members Subak Banyumati village of Uma Anyar about the impact caused by pollution of methane produced from cow dung and has made effort to empower community members Subak Banyumati to develop a system of integrated agriculture between agriculture, animal husbandry, and use of technology to increase the added value cow manure through training "Utilization of cow manure as a Source of Household Scale Biogas". With the implementation of this community service program Subak Banyumati community members are able to make the installation of household scale biogas to produce methane gas for cooking and to operate it. Thus the villagers of Ume Anyar in general and members of the community Subak Banyumati in particular able to use cattle dung as material biogas and able to make compost in a shorter time than before, and no less important is the community contribute to reducing air pollution by methane gas.